Xq25 duplications encompassing GRIA3 and STAG2 genes in two families convey recognizable X‐linked intellectual disability with distinctive facial appearance. Issue 6 (1st May 2013) - Philippe, Anne; Malan, Valérie; Jacquemont, Marie‐Line; Boddaert, Nathalie; Bonnefont, Jean‐Paul; Odent, Sylvie; Munnich, Arnold; Colleaux, Laurence; Cormier‐Daire, Valérie
Abstract We report here on two patients with Xq25 duplication encompassing GRIA3 gene, encoding glutamate receptor, ionotropic, AMPA subunit 3. The first case of Xq25 duplication was identified using genome‐wide array comparative genomic hybridization (array‐CGH) in a 24‐year‐old patient with syndromic intellectual disability. Based on similar facial features, we clinically suspected a second case of Xq25 duplication in a 4‐year‐old boy with intellectual disabilty. This duplication was confirmed by multiplex ligation‐dependent probe amplification (MLPA) of the GRIA3 gene, as well as by fluorescence in situ hybridization (FISH) and further refined by array‐CGH. We suggest that Xq25 duplication is responsible for a novel clinically recognizable X‐linked intellectual disability. Finally, the review of so far published Xq25 duplications support, in addition to the role of GRIA3 gene, a potential contribution of the duplication of STAG2 (Stromal Antigen 2) gene coding for the subunit SA1 of the cohesin complex in the clinical phenotype. © 2012 Wiley Periodicals, Inc.